Root and shoot biomass and nutrient composition of winter rye cover crop following corn and soybean - Swetabh Patel; Arshdeep Singh; John E. Sawyer; John P. Lundvall (Agrosystems, Geosciences & Environment)
Abstract Winter cereal rye (Secale cereale L.), a commonly used cover crop in corn (Zea mays L.) systems, has potential to scavenge soil NO3–N through a fibrous root system. This study aimed to quantify root and shoot biomass, carbon (C), and nitrogen (N) partitioning in rye cover crop at the time of termination in spring. This was a 1‐year study conducted at a site with a no‐till corn–soybean [Glycine max (L.) Merr.] rotation, rye drilled following grain crop harvest, and three N rates applied to corn (0, 135, and 225 kg N ha−1, respectively). Rye root biomass to 60‐cm depth following corn and 30‐cm depth following soybean was estimated using ingrowth tubes installed in the fall after rye seeding and removed at the time of rye termination in the spring. For rye, 48% and 62% of the total root biomass were present in the top 15‐cm depth, following corn and soybean, respectively. Overall, the shoot biomass, C, and N were significantly greater than for roots, with approximately two times more shoot than root material and only 33%–36% of total plant C and 17%–18% of total plant N in the root biomass. The C:N ratio of root biomass was consistently high (47–52) and at least double that of the shoot (16–23). With high C, low N, and high C:N ratio of the rye roots, inorganic‐N from soil or degrading shoot biomass could be immobilized with root degradation and reduce potential N recycling.